2013
DOI: 10.2527/jas.2012-5464
|View full text |Cite
|
Sign up to set email alerts
|

Effect of dietary levan fructan supplementation on growth performance, meat quality, relative organ weight, cecal microflora, and excreta noxious gas emission in broilers

Abstract: A total of 720 1-d-old male Ross broilers (BW of 48.0±0.3 g) were used to evaluate the effects of dietary levan fructan supplementation on growth performance, meat quality, relative organ weight, cecal microflora, and excreta noxious gas emission in broilers. This experiment lasted 31 d. Broilers were randomly allotted to 1 of 3 dietary treatments: 1) CON, basal diet, 2) CON+0.25% fructan (FC1), and 3) CON+0.50% fructan (FC2). Each treatment contained 16 pens with 15 chicks per pen. Broilers on levan fructan s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
19
1
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 39 publications
3
19
1
1
Order By: Relevance
“…A number of studies have demonstrated that addition of prebiotics could reduce noxious gas emissions from pigs (Awati et al 2006;Zhao et al 2013a;Cho & Kim 2015;Deng et al 2015), broilers (Zhao et al 2013b;Cho & Kim 2014), cats (Barry et al 2009) and dogs (Flickinger et al 2003). In the present study, PROFOS dietary treatment had reduced ammonia emission compared with PC, NC and PRO dietary treatments, indicating that combination of FOS and protease was more effective in reducing ammonia emissions than protease alone.…”
Section: Noxious Gas Emissionmentioning
confidence: 99%
“…A number of studies have demonstrated that addition of prebiotics could reduce noxious gas emissions from pigs (Awati et al 2006;Zhao et al 2013a;Cho & Kim 2015;Deng et al 2015), broilers (Zhao et al 2013b;Cho & Kim 2014), cats (Barry et al 2009) and dogs (Flickinger et al 2003). In the present study, PROFOS dietary treatment had reduced ammonia emission compared with PC, NC and PRO dietary treatments, indicating that combination of FOS and protease was more effective in reducing ammonia emissions than protease alone.…”
Section: Noxious Gas Emissionmentioning
confidence: 99%
“…The excreta samples were manually shaken for approximately 30 s to disrupt any crust formation on the surface of the slurry sample and to homogenize them. The adhesive plasters were punctured and 100 mL of headspace air was sampled approximately 2.0 cm above the excreta surface (Zhao et al, 2013). The air sampling was obtained on d 5.…”
Section: Laboratory Analysismentioning
confidence: 99%
“…The mechanism of antibiotics was involved with the fat and protein content of the feed and use of antibiotics in animal feed can moderate carcass quality (Humphrey et al 2002;Walker et al 2005;Pedroso et al 2006;Li & Kim 2013;Zhao et al 2013a;Zhou et al 2013a). Because of recent limitation of antibiotics addition, new feed additives such as herbs, spices, prebiotics, and probiotics have received increased attention as possible alternatives to antibiotics (Windisch et al 2008;Chu et al 2011;Huang et al 2012;Zhang et al 2012;Liu et al 2013;Wang et al 2013;Zhang & Kim 2013;Zhao et al 2013b;Cho & Kim 2014;Park & Kim 2014;Zhang & Kim 2014).…”
Section: Introductionmentioning
confidence: 99%